2002
DOI: 10.4141/a01-007
|View full text |Cite
|
Sign up to set email alerts
|

Feeding value in broiler chicken diets of a potato expressing a β-glucanase gene from Fibrobacter succinogenes

Abstract: . L'addition de 0,6 kg t -1 d'un cultivar transgénique de pomme de terre à une ration pour poulets de chair à base d'orge CDC Silky en tant que source de β-glucanase améliore (P < 0,05) la valorisation des aliments de 8,8 %. À la concentration de 1,2 kg t -1 , la viscosité des digest dans l'iléon diminue (P < 0.05) de 42 %. La pomme de terre transformée pourrait devenir un additif enzymatique intéressant avec une meilleure expression et/ou activité du gène.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The enzyme can be found in concentrations as high as 0.05% of the fresh tuber weight, with a specific activity of 3013 U/mg β-glucanase. The objective of a study conducted on broiler chickens was to evaluate this GM potato as a source of β-glucanase in barley-based chicken diets (Baah et al, 2002). Including this at 0.6 kg/t as a source of β-glucanase in barleybased diets for broiler chickens significantly improved feed conversion by 8.8% and, at 1.2 kg/t, significantly reduced ileal digesta viscosity by 42%.…”
Section: Transgenic Feeds and Biologically Active Substancesmentioning
confidence: 99%
See 1 more Smart Citation
“…The enzyme can be found in concentrations as high as 0.05% of the fresh tuber weight, with a specific activity of 3013 U/mg β-glucanase. The objective of a study conducted on broiler chickens was to evaluate this GM potato as a source of β-glucanase in barley-based chicken diets (Baah et al, 2002). Including this at 0.6 kg/t as a source of β-glucanase in barleybased diets for broiler chickens significantly improved feed conversion by 8.8% and, at 1.2 kg/t, significantly reduced ileal digesta viscosity by 42%.…”
Section: Transgenic Feeds and Biologically Active Substancesmentioning
confidence: 99%
“…However, performance parameters were significantly worse compared to the control group, where the chickens were fed a barley-based diet supplemented with a commercial β-glucanase preparation. The authors concluded that improved level and activity of expression is required in the transformed potato in order for it to have potential as an enzyme additive to barley-based diets (Baah et al, 2002).…”
Section: Transgenic Feeds and Biologically Active Substancesmentioning
confidence: 99%
“…For example, transgenic rice, corn, and canola overexpressing phytase from a bacterial origin supplemented in poultry feed resulted in significant improvements in nutritional value and a remarkable reduction in phosphorus excretion (Chen et al ., 2013 ; Hamada et al ., 2006 ; Hong et al ., 2004 ; Nyannor et al ., 2007 ; Zhang et al ., 2000 ). Broiler chickens fed with β‐glucanase from transgenic potatoes expressing β‐glucanase from Fibrobacter succinogenes had significantly improved feed conversion and reduced ileal digesta viscosity (Baah et al ., 2002 ). The expression of xylanase from Streptomyces olivaceoviridis in transgenic potatoes provides an alternative to present‐day xylanase additives to animal feed (Yang et al ., 2007 ).…”
Section: Introductionmentioning
confidence: 99%